Lack of management: a case study of Jurutera Artecon Sdn Bhd. - Mahziah Mahmud (2017)
Engineering has always being a vital product that is needed by client for every project. The need for engineering was noticed by the developer and the government where they provide the projects that can be designed and constructed for public use. These clients are more likely to choose the most well-known engineering company to pursue their projects. The designed plan prepared by the engineering company is usually come from the investigation and discussion between the clients and the engineers. Apart from the engineering company, there a various type of engineering company ranging from land survey to quantity survey. The difference between the engineering inside government and the private sector can be seen where the engineers working for the government substitute the projects to the engineering company in the private sectors to design the projects. Furthermore, most of the engineering companies have been established more than 10 years which mean that the companies have a lot of experience in designing and constructing. Engineering company is known as a place where the engineers, administrative and accountant department work under a roof together. Engineering company has grown everywhere in the world but they are divided into various type of engineering expertise. They could be a civil engineering company, land survey company, mechanical and electrical company and quantity surveyor company. The government is more likely to give a chance to a new engineering company to accept the project, design and construct them as an initiative to let them to learn and gain the experience. One of the civil engineering company in Kuching named Jurutera Artecon Sdn Bhd has been established since 2000 to meet the demands of federal and state government who want to realize a dream and facilities for the citizen and public. Jurutera Artecon Sdn Bhd was created to provide the engineering expertise in civil, road, building and other structure based on the given projects. In addition, the clients who invite Jurutera Artecon Sdn Bhd to do their project have the opportunity to know well about this company and keeping the details of this company for the future recall. The community of engineers around Kuching is large as a lot of the engineering companies try to communicate and form a group of expertise to solve a difficult engineering problem. The engineering company is usually furnished with several technology facilities like desktop computer, A1 printer, A3 printer, server system, wireless modem, security system and engineering and accountant software to ease the staff jobs inside the company. The demand from the government and also from the private sectors encourages the establishment of this engineering company at the strategic place near to other several engineering companies. Hence, the competition within Kuching area for this engineering company is medium compared to other part of the city. The engineering & construction company can be combined to create better attractive package for the government to consider the better projects in the future. The competition amongst the engineering companies could be a challenge for Jurutera Artecon Sdn Bhd as many engineering companies have growth up around Sarawak.. To sustain in the engineering field industry, various analysis need to be done to prolong this engineering company’s operation. STEEPLE analysis, SWOT analysis and Service Positioning are the methods that required to be used for analyzing the market of this engineering company. The measurement and strategies of the engineering company could be implemented thorough feedback from the clients, collection of information from the public, survey poll and reading of published of successful engineering company around Kuching where it would be hard for other predecessor to imitate or follow in the future. To create value amongst the clients who visit Jurutera Artecon Sdn Bhd, many alternatives and future plans have been prepared so that Jurutera Artecon Sdn Bhd could develop well in engineering field industry that not only in Kuching but also around Malaysia.